2007
DOI: 10.5511/plantbiotechnology.24.261
|View full text |Cite
|
Sign up to set email alerts
|

Sulfur-responsive promoter of sulfate transporter gene is potentially useful to detect and quantify selenate and chromate

Abstract: Heavy metals are highly toxic for living organisms when excess amounts exist in the environment (Salt et al. 1998;Kovalchuk et al. 2001). Soils and water contaminated with heavy metals cause major environmental and human health problems. During the last few decades, phytoremediation and plant-based assays for cleanup and monitoring of these contaminated environments have been developed (Salt et al. 1998;Kovalchuk et al. 2001;Krizek et al. 2003;Pilon-Smits 2005). These methods take advantage of the sedentary na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 18 publications
1
2
0
Order By: Relevance
“…3). It is possible that chromate affects plant viability more severely than selenate does, causing a distortion in the expression of the GFP reporter gene in transgenic plants at relatively high concentrations, as also suggested in previous studies (Maruyama-Nakashita et al 2007;Schiavon et al 2007).…”
Section: Gfp Accumulation In 1;2pg2t Plants Can Be a More Sensitive Isupporting
confidence: 52%
See 1 more Smart Citation
“…3). It is possible that chromate affects plant viability more severely than selenate does, causing a distortion in the expression of the GFP reporter gene in transgenic plants at relatively high concentrations, as also suggested in previous studies (Maruyama-Nakashita et al 2007;Schiavon et al 2007).…”
Section: Gfp Accumulation In 1;2pg2t Plants Can Be a More Sensitive Isupporting
confidence: 52%
“…P SULTR1;2 -GFP transgenic plants express GFP under the control of SULTR1;2 promoter, and GFP is accumulated in association with the increasing levels of SULTR1;2 mRNA (Maruyama-Nakashita et al 2004). Selenate and chromate can be detected by measuring GFP accumulation in P SULTR1;2 -GFP plants at concentrations of 10 μmol L −1 or higher, while selenate concentration can be roughly measured in a range of 1-30 μmol L −1 , enabling the estimation of external selenate concentration (Maruyama-Nakashita et al 2007). However, the detection limit of 10 μmol L −1 is 10 times higher than the environmental standard recommended by the World Health Organization (WHO 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, higher plants likely do not possess specific mechanisms to acquire this element [6]. Studies concerning the uptake of Cr from soil by different plant species have shown that Cr(III) is taken up passively, while Cr(VI) transport over plasma membranes is active and seems to be mediated by transporters of essential anions, such as sulfate [7][8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%